Application of vibrational signals to study and manipulate an insect vector: the case of Philaenus spumarius (Hemiptera: Aphrophoridae). Issue 10 (21st June 2022) - Avosani, Sabina; Ciolli, Marco; Verrastro, Vincenzo; Mazzoni, Valerio
Abstract: BACKGROUND: Vibrational stimuli can support pest management as they provide environmentally friendly methods to manipulate insect pest behaviors. Different vibrational stimuli were used to study and influence the behavior of the meadow spittlebug, Philaenus spumarius, the European vector of Xylella fastidiosa. In playback experiments, we tested the reactions of the spittlebug toward the male calling signals (test 1) and the male–male signal (test 2). In test 3, we evaluated the use of conspecific signals and noises to repel insects/disrupt mating. RESULTS: Test 1 provided new insights regarding the role of the male calling signal in intraspecific communication, in particular that this signal likely does not underlie aggregation or aggression toward conspecifics. Test 2 demonstrated that the male–male signal is used by males to express distress when physically interacting, whilst, when played back into a host plant, it has not any repellent effect on the spittlebug. Test 3A suggested that males exploit short silence gaps to localize the signaling partner, while test 3B showed that a continuous noise with a specific frequency range successfully disrupt mating, as only one male out of 20 localized the female on the plant. CONCLUSION: Playbacks obtained from prerecorded P. spumarius' signals were successfully used to accomplish ethological studies; even so, this approach did not show a real potential to be used as a control strategy. However, noises designed to mask the spittlebug signals significantly disrupted species mating and could integrate other techniques aimed at reducing the spread of X. fastidiosa after appropriate implementation. © 2022 Society of Chemical Industry. Abstract : Vibrational mating disruption in Philaenus spumarius (Aphrophoridae), vector of Xylella fastidiosa in Europe. A continuous noise transmitted to a host plant significantly reduced the number of mating pairs compared to the silent control group.